2019
DOI: 10.1590/rbz4820180259
|View full text |Cite
|
Sign up to set email alerts
|

Do live or inactive yeasts improve cattle ruminal environment?

Abstract: Ruminants Full-length research article Do live or inactive yeasts improve cattle ruminal environment? ABSTRACT-This research was conducted to investigate the effect of live and inactive sugarcane yeast on beef cattle voluntary intake, apparent digestibility of nutrients, ruminal pH, volatile fatty acids (VFA) concentrations, and ruminal ammonia. Five rumen-cannulated Nellore heifers were distributed in a 5×5 Latin square design, with five experimental periods of 15 days, with seven days for adaptation to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A increase in the concentration of NH 3 -N in the rumen is brought on by the high urea content of the CWYW and the quick hydrolysis of NH 3 -N by microbial enzymes 29 , 30 . In addition, changes in the proteolytic ruminal microorganism population and microbial disintegration of yeast cells into amino acids and NH 3 -N likely contributed to increased ruminal NH 3 -N in CWYW-fed animals 31 , 32 . Similarly, Suriyapha et al 2 found that the in vitro ruminal NH 3 -N concentration was increased when higher levels of CWYW replaced SBM.…”
Section: Discussionmentioning
confidence: 99%
“…A increase in the concentration of NH 3 -N in the rumen is brought on by the high urea content of the CWYW and the quick hydrolysis of NH 3 -N by microbial enzymes 29 , 30 . In addition, changes in the proteolytic ruminal microorganism population and microbial disintegration of yeast cells into amino acids and NH 3 -N likely contributed to increased ruminal NH 3 -N in CWYW-fed animals 31 , 32 . Similarly, Suriyapha et al 2 found that the in vitro ruminal NH 3 -N concentration was increased when higher levels of CWYW replaced SBM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, substantial increases in NH 3 -N concentrations occur in response to the microbial degradation of yeast cells [48,49]. Additionally, it could be due to the ability to provide stimulatory factors and even protein [50,51] to ruminal bacteria, or by changing in the abundance of microbes with proteolytic activity [52].…”
Section: In Vitro Ruminal Nh 3 -N Concentration and Ruminal Phmentioning
confidence: 99%
“…The greater ruminal NH 3 -N concentration at 4 h after feeding and the greater mean value for CWYW top-dressing compared to SBM top-dressing could be due to the greater CP content and CP digestibility of CWYW compared to SBM. Greater CP digestibility may have occurred as a result of the microbial disintegration of yeast cells [ 35 ] because of changes in the number of ruminal microorganisms with proteolytic activity [ 36 ] or to the ability to supply substances as stimulants, including protein, to bacteria in the rumen [ 37 , 38 ]. Another effect is the high level of NPN-urea in the CWYW, which causes increased levels of urea-N in the diet and the fast hydrolysis of NPN-urea into ruminal NH 3 -N by microbial enzymes, causing an elevation in ruminal NH 3 -N concentration [ 28 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…number of ruminal microorganisms with proteolytic activity [36] or to the ability to supply substances as stimulants, including protein, to bacteria in the rumen [37,38]. Another effect is the high level of NPN-urea in the CWYW, which causes increased levels of urea-N in the diet and the fast hydrolysis of NPN-urea into ruminal NH 3 -N by microbial enzymes, causing an elevation in ruminal NH 3 -N concentration [28,39].…”
Section: Plos Onementioning
confidence: 99%